Comparative analysis of immunomodulatory biomarker responses in clams Meretrix meretrix and Mactra veneriformis to waterborne cadmium exposure - Ren, Jiayun; Zhang, Zaiwang; Liu, Bingshen; Zhang, Qiong; Zhang, Jiqiang; Shang, Shuai (Frontiers in Marine Science, 2025)
Bivalves are important indicator species for cadmium (Cd) pollution, however, the differential detoxification and physiological responses to Cd exposure among co-occurring bivalve species have not been thoroughly studied. This study investigated alterations in metallothionein (MT), superoxide dismutase (SOD), and malondialdehyde (MDA) levels in the digestive gland and gills of clam species Meretrix meretrix and Mactra veneriformis following exposure to cadmium (Cd) at concentrations of 0.05, 0.10, and 0.15 mg/L over a period of 7 days. The results indicated that gill tissue, due to its direct contact with the environment and high metabolic activity, exhibited significantly greater variations in SOD, MT, and MDA contents compared to the digestive gland, rendering it more sensitive to Cd stress and suitable for acute toxicity monitoring. M. veneriformis demonstrated a faster and more pronounced response, with significant alterations in biomarker levels observed in the gills at early stages even under low Cd exposure. However, its detoxification system, specifically MT synthesis reached saturation more readily; under high Cd concentrations, biomarker levels peaked and subsequently declined rapidly, indicating the potential for the early onset of irreversible damage. In contrast, M. meretrix exhibited a gradual adaptive response, maintaining homeostasis via sustained MT synthesis, which reflects a higher tolerance to Cd stress. MDA contents showed significant early increases in both species’ gills, especially under low Cd concentrations, highlighting its value as both an early-warning indicator and a preferred biomarker for Cd pollution monitoring. The study provides candidate indicator species and identifies sensitive biomarkers for Cd biomonitoring in regions such as the Yellow River Delta and a theoretical basis for improving ecological risk assessment.